Analisa Performa Hybrid Ant Colony Optimization dalam Memecahkan Vehicle Routing Problem with Time Windows. - Timothy Handi Wibawa; Rolly Intan (Jurnal Infra, 2018)
In modern times, humans have been helped by many technological developments. One such field is the goods delivery field, called the Vehicle Routing Problem (VRP). Vehicle Routing Problem is a matter of where there is a freight fleet that has to deliver a certain amount of goods to various customers. The solution sought is the shortest route the fleet can take.,Hybrid Ant Colony Optimization (HACO)is an algorithm that is inspired from the foraging behaviour of ant species, that is one of the result of  development for Ant Colony Optimization. HACO has been published by Q. Ding et. al in 2012 to solve Vehicle Routing Problem with Time Windows. However, in that published journal, there were vagueness in some points like process time and memory usage. Therefore in this journal there is a need to review the performance of HACO to solve VRPTW, which will be done using unity. In this thesis is also discussed some development of HACO which are expected to fix and improve the result of HACO.